Incidental Colorectal Computed Tomography Abnormalities: Would You Send every Patient for a Colonoscopy?. (2008) - Stermer, Edy; Lavy, Alexandra; Rainis, Tova; Goldstein, Omer; Keren, Dean; Zeina, Abdel-Rauf
Abstract : BACKGROUND: The clinical significance of colorectal wall thickening (CRWT) in patients undergoing abdominal computed tomography (CT) has not yet been definitively established. OBJECTIVES: To compare alleged findings on abdominal CT with those of a follow-up colonoscopy. METHODS: Ninety-four consecutive patients found to have large-bowel abnormalities on abdominal CT were referred for colonoscopy. Of these patients, 48 were referred for a suspected colorectal tumour and 46 for CRWT. Colonoscopy was performed and findings were compared. RESULTS: Of the 48 suspected colorectal tumours, 34 were determined to be neoplastic lesions on colonoscopy. Of these, 26 were malignant and eight were benign. Colonoscopy revealed no abnormality in 30 of 46 patients with CRWT as a solitary finding, and revealed some abnormality in 16 patients (12 had diverticular disease, four had benign neoplastic lesions). CONCLUSIONS: CRWT as an incidental and solitary finding on CT should not be regarded as a pathology prompting a colonoscopy. Approximately two-thirds of the patients had a normal colonoscopy and the remaining patients had benign lesions (12 had diverticular disease and four had benign neoplastic lesions). However, many of these patients seem to warrant colonoscopy regardless of CT findings, particularly patients who have a family history of colorectal cancer, have positive fecal occult blood test results or who are older than 50 years of age.